Utility of picric acid and 2,4 dinitrophenol as chromogenic reagents for visible spectrophotometric quantification of alogliptin - A.V.V.N.K. Sunil Kumar; T.V. Reddy; C.B. Sekharan (Faculty of Pharmacy, Cairo University, 2017)
Two simple and sensitive visible spectrophotometric methods (A and B) were developed for the determination of alogliptin in bulk and in its tablet dosage forms. The methods use the reaction of alogliptin with picric acid (method A) or 2,4 dinitrophenol (method B) in the chloroform medium. The complex of alogliptin with picric acid (method A) or 2,4 dinitrophenol (method B) showed λmax at 415 nm and 430 nm respectively. The different conditions affecting the formation and stability of the complexes were optimized. The methods were validated statistically according to ICH. The calibration curve is linear over the concentration range of 10-60 μg ml−1 and 10-50 μg ml−1 for methods A and B, respectively. The proposed methods were successfully applied for the assay of alogliptin in tablets with good recoveries. Interference was not observed from common tablet excipients.